Profile of prehospital care in the countryside of Maranhão: a cross-sectional study (Revista Científica Integrada, 2025)
Objective: To evaluate the profile of care provided by the Mobile Emergency Care Service in a countryside of Maranhão, between 2021 and 2022. Methods: This is an analytical, descriptive, cross-sectional, and quantitative study conducted between July and September 2023. Data were collected from occurrence reports provided by the SAMU Coordination of Coroatá, Maranhão. The variables analyzed included the year of occurrence, sex, age group, nature of the call, and type of unit. Data analysis was performed using descriptive statistics to describe and summarize the information. The data were organized in Microsoft Excel (version 2016) and analyzed using the Statistical Package for the Social Sciences (SPSS), version 28.0.1. The study was approved by the Research Ethics Committee. Results: A total of 19,331 prehospital occurrences were analyzed, with many users being female (60.14%) and aged 60 years or older (36.08%). Most of the calls were of clinical (77.83%) and obstetric (7.04%) nature, with most occurrences attended by Basic Life Support Units (83.6%). Conclusion: The characterization of the care provided allowed for a better understanding of the profile of prehospital occurrences in the interior of Maranhão. Therefore, it is crucial to ensure the accurate recording of occurrence reports, promote the continuous training of professionals, and strengthen the oversight of professional practice to improve the quality and efficiency of the services provided.
Keywords: Emergencies; Emergency Medical Services; Health Profile